The role of fluid temperature and form on endurance performance in the heat - Tan, P. M. S.; Lee, J. K. W. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Exercising in the heat often results in an excessive increase in body core temperature, which can be detrimental to health and endurance performance. Research in recent years has shifted toward the optimum temperature at which drinks should be ingested. The ingestion of cold drinks can reduce body core temperature before exercise but less so during exercise. Temperature of drinks does not seem to have an effect on the rate of gastric emptying and intestinal absorption. Manipulating the specific heat capacity of a solution can further induce a greater heat sink. Ingestion of ice slurry exploits the additional energy required to convert the solution from ice to water (enthalpy of fusion). Body core temperature is occasionally observed to be higher at the point of exhaustion with the ingestion of ice slurry. There is growing evidence to suggest that ingesting ice slurry is an effective and practical strategy to prevent excessive rise of body core temperature and improve endurance performance. This information is especially important when only a fixed amount of fluid is allowed to be carried, often seen in some ultra-endurance events and military operations. Future studies should evaluate the efficacy of ice slurry in various exercise and environmental conditions.